3 days to live eaudiobook - Patterson, James (2023)
The people closest to you can be your most dangerous enemies in this heart-pounding collection of three thrillers from master of suspense and New York Times bestselling author James Patterson. 3 Days to Live : A CIA-agent bride is on her European honeymoon when she and her husband are poisoned—leaving her seventy-two hours to take revenge (with Duane Swierczynski). Women and Children First : When a deal goes bad on a tech executive in Washington, DC, he turns an order to kill his family into a chance to relive his military glory days (with Bill Schweigart). The Housekeepers: A Los Angeles doctor trusts her two housekeepers, but when she's murdered in a botched attempt to steal drugs, the pair of grifters vie to control their former employer's estate—facing off against the Russian mob (with Julie Margaret Hogben).